Analysis of the Influence of River Water Quality on Public Health in Kolohipo, Laloeha Village, Kolaka District, Kolaka Regency - Sari, Rina Sardiana; Ningsi, Nurfitria; Ramadhan, Muhammad Fajri (Navigation Physics : Journal of Physics Education, 2025)
As the main water source for the surrounding environment, the Kolohipo River is very important. The river, a freshwater ecosystem, provides water for local industries, agriculture, and daily needs. However, the water quality of the Kolohipo River has declined drastically due to increasing human activities including intensive agriculture, domestic waste disposal, and deforestation throughout the river basin. Public health, environmental sustainability, and agricultural yields may be compromised by this decline in water quality. By monitoring physical, chemical, and biological parameters such as pH, dissolved oxygen, BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand), and heavy metal concentrations, this study attempts to assess the water quality of the Kolohipo River. heavy metals. This study also assesses the relationship between local water quality decline and human activities. The findings of this study are expected to assist initiatives to protect the river as an important resource for the Kolohipo community's way of life and offer suggestions to the community and authorities to manage and resolve water pollution issues. Kolohipo community.